KAJIAN SOSIOLINGUISTIK DIGITAL: STUDI KASUS PENGGUNAAN CAMPUR KODE KOMUNITAS MAHASISWA TORAJA DALAM INTERAKSI WHATSAPP - Ita Sarmita Samad; Sry Wahyuni (Jurnal Prasasti Ilmu, 2026)
This study aims to identify forms of code mixing, analyze its use function, and examine the social and linguistic factors that affect the practice of mixing code in Toraja students' WhatsApp interactions. This study uses a qualitative approach with a descriptive design in the framework of digital sociolinguistics. Data in the form of conversations in WhatsApp groups was collected through non-participatory observation techniques and documentation with screenshots, then transcribed and analyzed using content analysis techniques through data reduction, classification, and interpretation stages. The results of the study showed that the code mix used was dominated by lexical forms (insertion), accompanied by morphological forms and the use of digital language (internet slang). The function of mixing codes includes marking regional identity, forming social solidarity, communication efficiency, and emotional expression through multimodal elements such as emojis. The practice of mixing code is influenced by social identity, interpersonal relationships, multilingual competence, characteristics of digital media, and global cultural influences, which as a whole reflect the dynamics of language use in multilingual societies in the digital age.